Planning for sustainable travel : integrating spatial planning and transport - Hickman, R; Seaborn, C; Headicar, P; Banister, D (Routledge, 2010)
Travel is an essential part of everyday life and today most journeys are multimodal. It is the total travel experience that counts and integrated transport must reduce the inconvenience of transfers between modes. Most research and many publications on transport policy advocate sustainable transport, but the priority given to integration has been negligible. Yet integration is one of the most important means to advance sustainable transport and sustainability more generally. While integrated transport systems are seen to be an ideal, there is a failure to make the transition from policy to practice. The authors argue that the achievement of sustainable transport is still a dream, as an integrated transport policy is a prerequisite for a sustainable transport system. It is only when the two concepts of sustainability and integration operate in the same direction and in a positive way that real progress can be made. In this book, transportation experts from across the world have addressed the questions about what is integration, why is it so important and why is it so hard to achieve? The book provides an in-depth analysis of these issues and it aims to provide a better understanding of the subject, about what should be strived for, about what is realistic to expect, and about how to move forward towards a more integrated provision of transport infrastructure, services and management.